A Freudian Psychoanalytic Analysis of the Main Character in Edgar Allan Poe's The Tell-Tale Heart - Salwa Naila Humaira; Tengku Thyrhaya Zein; Zaskia Fatimah; Cecilia Novalisa Situmorang; Salsa Aila; Ratu Aliqa Syahkirana Idham (Medan Resource Center, 2026)
This study investigates the psychological dynamics of the main character in Edgar Allan Poe’s The Tell-Tale Heart through the lens of Sigmund Freud’s psychoanalytic theory. The research addresses the question of how the interaction of the id, ego, and superego shapes the protagonist’s psychological conflict and influences his irrational behavior throughout the narrative. Employing a descriptive qualitative design, the study utilizes textual analysis to interpret the character’s thoughts, actions, and emotional responses based on Freud’s structural model of personality. The findings reveal that the protagonist’s obsessive fixation on the old man’s eye originates from the id, whereas the ego proves incapable of regulating these instinctual impulses in a rational manner. Following the murder, the superego intensifies feelings of guilt and moral anxiety, ultimately manifesting in auditory hallucinations that compel the protagonist to confess his crime. The study concludes that Freud’s psychoanalytic framework offers a comprehensive explanation of the protagonist’s internal conflict, illustrating that unconscious psychological forces significantly shape human behavior and decision-making in literary narratives while enriching the application of psychoanalytic literary criticism.